Modelling of protons spectra encountered in space using medical accelerator and its microdosimetric characterization. Issue 8 (15th April 2021) - Peracchi, S.; James, B.; Psoroulas, S.; Grossmann, M.; Meer, D.; Bolst, D.; Pastuovic, Z.; Vohradsky, J.; Guatelli, S.; Prokopovich, D.A.; Petasecca, M.; Lerch, M. L.F.; et al.
Highlights: LEO proton spectra simulated by GEANT4 are delivered using clinical accelerators. The paper shows a methodology to program a treatment planning system. The dose delivered is modulated on a realistic polienergetic fluence spectrum. SOI microdosimeter measured the quality factor of proton field. The dose equivalent Hp(10) associated to the proton field is measured. Abstract: Radiation environments in space are mainly composed of protons coming from the Galactic Cosmic Rays (GCRs) pervading the universe, the Solar Particle Events (SPEs) resulting from solar flares and coronal mass ejections, and the two Van Allen Belts surrounding the Earth due to the presence of the geomagnetic field trapping charged particles. Their wide spectra of energies up to hundreds of GeV imply diverse radiobiological effects to astronauts and radiation damage to electronics in the spacecraft. Even if lower in abundance, heavy ions such as He, C, O, Si, Fe are present in space and constitute an even bigger hazard due to their high penetrability and high linear energy transfer (LET). Most irradiation facilities available for research and testing worldwide provide usually only monoenergetic beams of high-energy protons or other heavier particles limiting studies of radiobiological effects and effects on electronics to a set of discrete energies. This paper introduces a procedure where a proton fluence spectra of interest for space radiation protection, previously generated by Monte Carlo simulations was delivered using a clinical proton therapy accelerator. Particularly, it reports the first results of modelling a proton radiation field in space in the energy range from 70 to 230 MeV during a single experimental session by programming a treatment planning system (TPS) to deliver required proton irradiation energies. Moreover, the angular distribution of the proton irradiation field has been varied to reproduce the isotropic exposure experienced by humans in space. The obtained proton radiation field was characterized using a 3D sensitive volume SOI microdosimeter developed by the Centre for Medical Radiation Physics (CMRP), University of Wollongong, Australia.